2020
DOI: 10.1126/sciadv.abb9116
|View full text |Cite
|
Sign up to set email alerts
|

Paternal deprivation impairs social behavior putatively via epigenetic modification to lateral septum vasopressin receptor

Abstract: Although it is well appreciated that the early-life social environment asserts subsequent long-term consequences on offspring brain and behavior, the specific mechanisms that account for this relationship remain poorly understood. Using a novel assay that forced biparental pairs or single mothers to prioritize caring for offspring or themselves, we investigated the impact of parental variation on adult expression of nonapeptide-modulated behaviors in prairie voles. We demonstrated that single mothers compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 53 publications
1
40
0
1
Order By: Relevance
“…The human literature has found that males are more sensitive to the preserving effects of mating partnerships. Similar male-biased sensitivity among prairie voles has been reported as a result of single-gene DNA methylation associated with early life social experience on later social behavior (specifically social approach) 24 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The human literature has found that males are more sensitive to the preserving effects of mating partnerships. Similar male-biased sensitivity among prairie voles has been reported as a result of single-gene DNA methylation associated with early life social experience on later social behavior (specifically social approach) 24 .…”
Section: Discussionsupporting
confidence: 69%
“…Although certain epigenetic mechanisms have recently been studied in the context of pair bonding and parental care in prairie voles [20][21][22][23][24] , the impact of pair bonding on age-related epigenetic changes is an important consideration that has not received attention until now. DNA methylation (DNAm), the most studied epigenetic modification, chiefly occurs on cytosines followed by guanine residues (CpG) along the 5'3' direction 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AVPR1As located outside of these regions such as in the ventral pallidum, LS, and retrosplenial cortex are also known to be involved in different types of social interactions (Boender & Young, 2020). For example, AVPR1As in the ventral pallidum facilitate partner-preference formation (Lim & Young, 2004), while epigenetic modification of AVPR1As in the LS has recently been shown to be associated with impairment of parental care driven by paternal deprivation (Kelly et al, 2020).…”
Section: Role Of Hormone Receptors and Neuropeptides In The Social Brain Networkmentioning
confidence: 99%
“…An initial study by Ahern and Young 18 demonstrated that both male and female prairie vole offspring reared under conditions of paternal absence demonstrated inhibited partner preference formation. In a subsequent study, it was found that prairie vole mothers left to rear offspring without supplemental care from a mate did not compensate for the reduction of care resultant of the father's absence, 19 a finding that has been replicated 20 (but see also the study by Kelly et al 21 in which mothers compensate for paternal absence when additional environmental challenges are applied). Accordingly, offspring reared under conditions of paternal absence also experienced a general decline in parental investment throughout their pre‐weaning development.…”
Section: Introductionmentioning
confidence: 95%